Iron and Cobalt Phthalocyanine Embedded Electrospun Carbon Nanofiber-Based Catalysts for Anion Exchange Membrane Fuel Cell Cathode - Zagal-Moya, J; Zagal-Moya, J (Academic Press, 2023)
The successful implementation of renewable energy transition assumes the introduction and widespread use of zero-emission and sustainable energy conversion devices. Anion-exchange membrane fuel cell (AEMFC) is one of the appliances that meets the prescribed criteria. In this study, Fe(II) phthalocyanine and Co(II) phthalocyanine co-doped polyacrylonitrile-based electrospun carbon nanofibre (CNF) catalysts were prepared via pyrolysis. The influence of carbonisation temperature, acid leaching conditions, presence of ionic liquid (IL) as porogen, and the metal phthalocyanine content were investigated. Physical characterisation revealed the nanofibrous structure, high specific surface area, presence of Co-Nx, Fe-Nx sites, and different N-species with high oxygen reduction reaction (ORR) activity. The catalyst material with the highest ORR performance, D-MN4-CNF-IL-A, showed a half-wave potential of 857 ± 6 mV vs. reversible hydrogen electrode in 0.1 M KOH and the maximum power density value of 231 mW cm−2 when applied as a cathode catalyst in the AEMFC. © 2023 Elsevier Inc.